A Systematic Review of Therapeutic Recreation Camp Impact on Families of Children With Chronic Health Conditions. (19th February 2019) - Rea, Kelly E; Quast, Lauren F; Stolz, Mary Gray; Blount, Ronald L
Abstract: Objective: Parents and siblings of children with chronic illnesses are at increased risk for experiencing psychosocial difficulties. Therapeutic recreation camps have become increasingly popular among these families. The current systematic literature review provides a synthesis of research on how these camps impact the parents and siblings of children facing a variety of chronic health conditions. Methods: Databases searched: PubMed, PsycInfo, SportDISCUS, and Health Source Nursing/Academic Edition. Inclusion criteria included publication in a peer-reviewed journal between January 2000 and May 2018, written in the English language, and assessment of parent, sibling, or family outcomes. Results: Twenty-one studies were included. Results indicated that camp attendance relates to positive changes in parent and sibling psychosocial outcomes. Additionally, parents report camp to be a place of social support and respite from daily life, and siblings find camp to be enjoyable and a place of belonging. Given the limited number of methodologically sound studies examining family functioning, it is not yet clear the extent to which camp influences family-level outcomes. Conclusion: Overall, camp appears to have a positive impact on parents and siblings across chronic illness populations. Future research should specifically assess family outcomes, including communication and family functioning, and the impact of incorporating well-defined interventions and education programming into the traditional therapeutic recreation camp experience.